The development of students' worksheets using project based learning (PjBL) in improving higher order thinking skills (HOTs) and time management skills of students. Issue 1 (March 2021) - Santoso, A M; Primandiri, P R; Zubaidah, S; Amin, M
Abstract: Time management skills cannot be released with student learning activities in project-based learning. The development of PjBL-based student worksheets is expected to not only empower higher-level thinking skills but also students' time management. This study aims to develop project-based learning worksheets. This research was conducted by using the Plomp design research consisting of preliminary, prototyping, and assessment phases. The results of this research revealed that both of critical thinking and creative thinking skills had increased (medium category) and it was have an impact on improving student time management with an effect size of 14, 18 (very high). There was a`positive correlation between HOTs with students' time management skill (r=0, 82). Both of critical thinking and creative thinking were involving mental processes at each stage of project implementation so students must be able to manage their time well. This happens repeatedly and structured. Finally, the implementation of PjBL-based student's worksheet can improve student's higher-order thinking skills and time management skills.